Bestlink College of the Philippines Fire Disaster Preparedness; Basis for Fire Safety Awareness: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Of all the natural disasters, fire is the only one that is both beneficial to man and his environment as well as destructive and deadly. Man has depended on it for centuries for things from cooking and heating to a major source of lighting. And yet, thousands of people die each year as a result of either house fires or wildfires in some places. When it gets out of hand, early warning from a smoke detector or knowledge and skill on how to calmly escape a fire situation is vital. A thorough assessment of the wiring system/ electrical connection, other fire hazards, and possible causes of fire should be conducted to eliminate the possibility of fire. The study also seeks to determine if both personnel and students are aware of the different drills, procedures, and workarounds in school if there are ever actual fire breaks.The study will utilize the descriptive method of research to show the respondents' appraisal of the fire safety readiness of the Bestlink College of the Philippines. The study contains One Hundred (100) limited respondents. It includes thirty (30) employees and seventy (70) selected students of the Bestlink College of the Philippines. The selected respondents were chosen through purposive sampling. In this study, the main gathering instrument used was the survey questionnaire formulated by the researchers with the guidance of the thesis adviser.The respondents agreed that in every floor there must be available fire hose with a mean score of 2.9 interpreted as agree. In terms of training, the respondents agreed that the school must conduct a regular fire drills. There are also available signages posted in every exit of the school. According to the respondents Fire safety awareness is important to prevent the fire, keeping the sources of fuel and ignition apart.Bestlink College of the Philippines Fire Disaster Preparedness is ready for any fire incident that might occur. The problems encountered that affect the school preparedness, such as “Lack of well-labeled exits,” are the main concern of the respondents. Measures may be proposed to improve the fire safety of the institution for continuous safety. “Everyone in the school should know how to evacuate in the event of a fire. There should be a designated fire exit and a backup exit in case the first one is blocked.”
Keywords: fire safety; fire preparedness; fire disaster preparedness